2016
DOI: 10.1177/0829573516644554
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Combined Academic and Personal Counselling Initiative for Post-Secondary Student Retention

Abstract: This study investigated the effectiveness of a combined academic and personal counselling initiative on student performance and emotional well-being outcomes of 289 at-risk students at a Canadian University. Criterion for risk included academic struggles, mental health distress, or both. The program was developed to be tailored to individual needs, and students participated in weekly counselling sessions over the course of 1 academic year. Results showed significant overall increases in student grade point ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The increasingly well-established connection between mental health and retention offers a window of opportunity for post-secondary institutions to improve their retention rates by prioritising the implementation of policies and practices that not only aim to provide academic support to students in need, but also mental health and emotional support (Robbins et al, 2009). The FITA programme is an example of an accessible initiative that does not just react to the student mental health crisis, but also attempts to curb it by functioning as a preventative measure that identifies and supports at-risk students, in addition to acting as a retention programme (Abelman & Molina, 2002;Bilodeau & Meissner, 2016;Heisserer & Parette, 2002;Meissner et al, 2017). Going forward, colleges and universities interested in increasing their retention rates should prioritise the implementation of policies and practices that develop and implement evidence-based programming designed to support both the mental health and academic needs of at-risk students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increasingly well-established connection between mental health and retention offers a window of opportunity for post-secondary institutions to improve their retention rates by prioritising the implementation of policies and practices that not only aim to provide academic support to students in need, but also mental health and emotional support (Robbins et al, 2009). The FITA programme is an example of an accessible initiative that does not just react to the student mental health crisis, but also attempts to curb it by functioning as a preventative measure that identifies and supports at-risk students, in addition to acting as a retention programme (Abelman & Molina, 2002;Bilodeau & Meissner, 2016;Heisserer & Parette, 2002;Meissner et al, 2017). Going forward, colleges and universities interested in increasing their retention rates should prioritise the implementation of policies and practices that develop and implement evidence-based programming designed to support both the mental health and academic needs of at-risk students.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, the programme has been piloted at several post-secondary institutions across Ontario and results have consistently shown improvement in both student mental health and retention (Antunes-Alves et al, 2017;Bilodeau & Meissner, 2016;Meissner & Konecki, 2015). Designed to address both personal and academic issues, FITA uses a holistic and humanistic approach that is tailored to the individual needs of at-risk students who selfrefer to the programme and qualify based on grades and mental distress evaluations.…”
Section: Fita : a Comb Ined Interventi On To Improve Mental He Althmentioning
confidence: 99%
See 2 more Smart Citations
“…This programme is unique in its focus on the therapeutic relationship in delivering academic support and promoting psychological wellbeing. Results of these studies confirmed that the intervention was linked to an increase in psychological wellness and overall academic performance and academic functioning in students with differential needs and was thus identified as a promising two-pronged approach to promoting student academic success and retention (Antunes-Alves & Langmuir, 2021; Bilodeau & Meissner, 2016).…”
Section: Research Objectivesmentioning
confidence: 77%